Egg Cannibalism Varies With Sex, Reproductive Status, and Egg and Nymph Ages in Arma custos (Hemiptera: Asopinae) - Wu, Shaolong; Zeng, Weiai; Deng, Wan; Li, Mi; Hu, Wei; Cai, Hailin; Li, Youzhi; Xie, Pengfei; Tan, Lin; Zhou, Zhicheng (Frontiers in Ecology and Evolution, 2021)
Background: Egg cannibalism is common in nature. In China, Arma chinensis (Hemiptera: Asopinae) has been widely used as a natural enemy to control agricultural and forestry pests. A previous study showed that adult A. chinensis will devour its eggs. However, no research has investigated the interaction between A. chinensis cannabilism and egg development. Clarifying the mechanisms involved in egg cannibalism by A. chinensis improves our understanding of the evolutionary relationships for more efficient mass rearing and biological control systems. Results: The first and second instar nymphs did not devour eggs. The third, fourth, and fifth instar nymphs devoured eggs. Younger eggs were more readily eaten than older eggs. Virgin females were less inclined to cannibalise eggs than gravid females. Neither A. chinensis nymphs nor female adults consumed all of the available eggs, allowing an emergence ratio of > 70 %. Conclusions: A. chinensis females exhibit a high tendency for egg cannibalism. Egg cannibalism varies with the developmental stage of the eggs, nymphs, and A. chinensis females. A. chinensis is a very useful natural enemy of agricultural and forestry pests for biocontrol programs. It limits the cannibalism of parental and non-parental eggs to ensure a continuous supply of insects.